Whose Preferences Matter for Redistribution: Cross-Country Evidence - Michel André Maréchal; Alain Cohn; Jeffrey Yusof; Raymond Fisman (Center for Economic Studies and ifo Institute (CESifo), 2023)
Using cross-sectional data from 93 countries, we investigate the relationship between the desired level of redistribution among citizens from different socioeconomic backgrounds and the actual extent of government redistribution. Our focus on redistribution arises from the inherent class conflicts it engenders in policy choices, allowing us to examine whose preferences are reflected in policy formulation. Contrary to prevailing assumptions regarding political influence, we find that the preferences of the lower socioeconomic group, rather than those of the median or upper strata, are most predictive of realized redistribution. This finding contradicts the expectations of both leading experts and regular citizens.
Keywords: H23; D72; D78; 330; elite capture; median voter theorem; preferences for redistribution